Transforming Public Sector Performance through Total Quality Management: The Role of Transformational Leadership and Digital Integration in Indonesia - Dida Novandika; Hari Risky Syahputra; Mohammad Fahmy Bin Rapaee; Nuriyah Nuriyah (J-MD Jurnal Manajemen Dakwah, 2025)
The study investigates how Total Quality Management (TQM) principles specifically customer focus, process orientation, and continuous improvement are applied within Indonesia’s public sector. It explores how transformational leadership and digital integration influence the effectiveness of TQM implementation in enhancing public service performance. Despite numerous policy initiatives to adopt TQM in Indonesia’s public institutions, the outcomes remain inconsistent. Rigid bureaucratic structures, limited resources, and weak organizational quality culture continue to impede effective implementation. There is limited empirical understanding of how leadership style and digitalization interact to support sustainable TQM adoption in developing-country contexts. This research employs a descriptive qualitative design using document analysis. Data were collected from government reports, regulatory frameworks, standard operating procedures (SOPs), and relevant scholarly literature. NVivo software was used to code and analyze themes related to leadership commitment, process management, and digital transformation in public organizations. The findings indicate that agencies with strong transformational leadership and data-driven processes demonstrate measurable improvements in efficiency and citizen satisfaction. However, widespread implementation remains hindered by bureaucratic inertia and lack of technological capacity. Digital integration significantly supports real-time performance monitoring, transparency, and continuous improvement initiatives. This study emphasizes the need for leadership development, sustained employee training, and technology infrastructure investment to institutionalize quality culture in the public sector. The results provide actionable insights for policymakers to align TQM principles with e-governance strategies to improve service delivery. This paper contributes a new integrative framework combining transformational leadership and digital transformation within the TQM model for developing countries. It advances the discourse by linking leadership behavior, technological capability, and organizational adaptability as synergistic enablers of sustainable quality management in the public sector. Keywords: Total Quality Management; public sector; transformational leadership; continuous improvement; information technology.